Foreign Direct Investment and Carbon Dioxide Emissions: Evidence from Capital of Vietnam - Minh, Ngo Ngoc (International Journal of Energy Economics and Policy, 2020)
The purpose of this paper is to investigate the relationship between carbon dioxide (CO2) emissions, foreign direct investment (FDI), income per capita and energy consumption (EC) in the capital of Vietnam from 1990 to 2015. The empirical results indicate that EC is a major contributor of environmental degradation while FDI marginally contribute to the current status. Moreover, a one-way causality is found to be running from carbon dioxide (CO2) emissions, EC, FDI to income in the long-run. Then, the new empirical findings suggest that municipal government should make urgent regulations to drastically the energy consumption especially for private cars and motorbikes to improve environmental quality in Hanoi. Keywords: Income Per Capita, Inward FDI, Energy Consumption, CO2 Emissions, Hanoi Capital, Vietnam JEL Classifications: F21, O44, Q43 DOI: https://doi.org/10.32479/ijeep.9023